Preventing tissue fibrosis by local biomaterials interfacing of specific cryptic extracellular matrix information - Christine-Maria Horejs (Nature Portfolio, 2017)
Matrix metalloproteinase enzymes are widely known to contribute to the breakdown of tissues. Here, the authors utilise a biomaterial substrate functionalised with a laminin fragment to modulate the expression of these enzymes, subsequently controlling the integrity of tissue.